From compliance to commitment: centralization and public service motivation in different administrative regimes. Issue 5 (1st August 2016) - Prysmakova, Palina
Abstract : Purpose: Building on institutional theories, the article tests the relationship of organizational centralization and public service motivation (PSM), and explores country's centralization effect on it. Design/methodology/approach: The quantitative analysis of 390 responses from 42 social care and labor market public service providers operating in two countries with opposite administrative regimes – decentralized Poland and centralized Belarus. Findings: The Polish sample confirms previous observations. Organizational centralization correlates with PSM, while PMS dimensions do not act in concert. In contrast to others, self-sacrifice is positively associated with increased centralization. A country's context has a strong mediating effect. The Belarusian sample revealed no relationship between organizational centralization and PSM. Because the main difference with Poland lies in the politico-administrative organization of the public sector, the findings suggest further examination of the county's centralization effects. Democracy is not an imperative for higher PSM. Belarusian employees scored higher than the Polish on attraction to public service. Centralization of state administration does not necessarily indicate higher centralization in separate executive units. Polish organizations scored similar or higher on the questions of organizational centralization. Research limitations/implications: Context factors correlate differently with separate PSM dimensions, therefore, researchers should always look at PSM as a complex concept. Robust assertions about country's centralization effect will require further tests on a larger sample of countries with different administrative regimes. Practical implications: HR managers in decentralized Poland could modify employees' PSM behavior by altering the centralization level of an organization. In highly centralized Belarus, employees' PSM is less responsive to centralization changes, thus, HR managers should recruit individuals with the initially high PSM. Originality/value: First PSM study with the primary data collected in a nondemocratic country; first study to simultaneously address centralization on organizational and country levels.